Alüminyum ve bazı organik asitlerin etkileşiminin spektrometrik ve kromatografik yöntemlerle tayini - Yenigül, Elçin (My University, 2006)
ABSTRACT The interest to aluminium which is one of the most abundant element, increases with theknowledge of its harms to biologic and natural systems with its increase of usage recently.Aluminium is an element that can cause norological diseases such as Alzheimer, Parkinsonwith its harm on human metabolism.Bearing this in mind, some spectrometric determination techniques with some reagents areapplied to determine the uptake of aluminium from the solution or to examine this uptake inthe presence of different organic acids environment. Moreover, it is possible to clarify itschemical forms with chromotographic determination. Most part of the study was holded inRoyal Liverpool University Hospital s Clinical Biochemistry Laboratories for the project thatwas supported by British Council and some of it at Czech University, Agricultural Faculty,Soil Science Department for clarifying this effects of aluminium.In this study, tiron and pyrocathecol violet were used to determine aluminiumspectrometrically. Additionally, the effects of some compounds such as sitric acid, maltol,lactate, acetate, acethylacetonate were examined for the determination of aluminium in thepresence of these reagents. Also behaviour of (-)epicathecin, (-)epigallocatechin were studiedfor tiron.Some synthetic solutions were examined to separate the chemical forms of aluminium at pH2,5 and it was tried to determine the forms at this pH by chromotographic determination.Additionally, the aluminium content in some daily used fruit juices and tea samples wereanalysed with GFAAS and ICP-OES methods.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2006
Keywords: Aliminyumun özellikleri; Sitrik asit ve yapısı; Maltol ve yapısı; Aluminium; Spectrometric determination; Tiron; Pyrocathecol violet; Chemical forms of aluminium